GEOLOGICAL, GEOMORPHOLOGICAL AND TECTONIC STRUCTURE OF NE ATTICA AND SEISMIC HAZARD IMPLICATIONS FOR THE NORTHERN EDGE OF THE ATHENS PLAIN - Papanikolaou, D.; Papanikolaou, I. (Bulletin of the Geological Society of Greece, 2007)
A synthesis of geology, geomorphology and tectonics has been compiled regarding the NE part of Attica. This synthesis helps us clarify how old and new structures interrelate and interact to provide the present day setting. Geological, geomorphological maps, and cross-sections are provided to help us depict and extract data. The region of NE Attica forms a tilted tectonic block bounded by the Afidnai fault to the south and the Oropos fault to the north that rotates to the S-SW. This tilt produces southern trending flow directions draining the footwall within the block. Drainage basins are highly asymmetric due to the presence of active normal faults producing a combination of fault parallel and fault perpendicular flow directions. This block is also divided by a NNE-SSW detachment fault that separates the metamorphic units to the east from the unmetamorphic units to the west. It was active in Late Miocene-Early Pliocene and produced several hundred meters of debris-flow deposits. This detachment influences the geometry, style and intensity of deformation, but also the seismicity pattern. In particular, this detachment coincides with the line separating zone I (lowest category of seismic risk) from zone II of the national seismic building code. Finally, the Athens plain is bounded northwards by the active, but low slip-rate E-W trending, 14 km long, Afidnai fault.